PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGANDIMEDIASI OLEH KEPUASAN PELANGGANDI PT PERUSAHAAN GAS NEGARA, Tbk AREA DUMAI - Charly Simanullang; Alvi Furwanti Alwie; Yusni Maulida (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the effect of service quality and company image on customer loyalty, with customer satisfaction as a mediator, at PT Perusahaan Gas Negara, Tbk Dumai Area. PT Perusahaan Gas Negara, Tbk is a leading company in the gas sector, and understands the very important factors that influence customer loyalty in maintaining and increasing market share. This research was conducted in Dumai with the population being all household sector gas customers of PT. Perusahaan Gas Negara Tbk Dumai Area. The total population in the study is 8,873 active customers who are currently still using city gas products. The sampling technique used is probability sampling using the simple random sampling method The number of samples in this study is 368. Survey approach with primary data collection from active customers, using questionnaires to measure customer perceptions of service quality, company image, customer satisfaction, and their level of loyalty to PGN. The collected data is analyzed using statistical analysis, data analysis using the Partial Least Square (PLS) approach with component - or variant-based Structural Equation Modeling (SEM) equation models. The results of this study show that service quality has a positive and significant effect on customer satisfaction. The company's image also has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction proved to be a significant mediator between service quality and customer loyalty. That is, customer satisfaction plays a role in linking customer experience with their loyalty to PGN Dumai.As for company image, customer satisfaction is not a significant mediator of customer loyalty. The results of this study provide valuable insights into the importance of maintaining and improving service quality and company image to maximize customer satisfaction and ultimately increase customer loyalty. Companies may consider further investments in staff training, corporate image improvement, and efforts to improve customer satisfaction as part of their marketing strategy. This research also contributes to the literature in the field of marketing and management by confirming the important role of customer satisfaction as a mediator in the relationship between service quality, and customer loyalty. Keywords :